Misleading Claims, Customer Trust, and Skincare Repurchase Intention: A Systematic Literature Review - Asih Idha Listiyowati; Afifah, Nur; Mustaruddin; Rosnani, Titik (JURNAL MANAJEMEN MOTIVASI, 2026)
This systematic literature review examines how customer trust shapes skincare repurchase intention among female consumers, particularly in relation to misleading claims, greenwashing, digital credibility, product safety, and sustainability communication. Using the PRISMA approach, this study synthesized 41 studies from Scopus and related indexed sources published within the last ten years. The findings show that repurchase intention is influenced by e-WOM credibility, source credibility, brand image, perceived value, satisfaction, perceived risk, online community trust, product transparency, and ethical marketing. This review positions customer trust as a key mechanism linking misleading claims, perceived safety, and repurchase intention.